2004
DOI: 10.1007/s11137-005-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decomposition of hydrazine in weakly alkaline solutions on platinum nanoparticles

Abstract: The kinetics and stoichiometry of catalytic decomposition of hydrazine in 0.01 M NaOH solutions in the presence of unstabilized ([gray] colloid) and stabilized with sodium polyacrylate ([brown] colloid) platinum nanoparticles were studied. The main decomposition products are ammonia and N 2 with H 2 impurity (up to 1.5%), i.e., hydrazine decomposition predominantly follows the stoichiometric equation 3N 2 H 4 = 4NH 3 + N 2 . The catalytic activity was studied as influenced by nanoparticle size distribution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Colloidal platinum nanoparticles as catalysts for electron-transfer reaction were extensively investigated (27)(28)(29). Furthermore, Aiuchi (30) and Anan'ev (31) reported that colloidal platinum nanoparticles as a catalyst could transfer electrons to hydrogen peroxide and hydrazine to cause them decompose in weakly alkaline solutions. As for the mechanism of hydrogen peroxide decomposition, many possible mechanisms for this catalysis have been proposed.…”
Section: Possible CL Enhancement Mechanism Discussionmentioning
confidence: 99%
“…Colloidal platinum nanoparticles as catalysts for electron-transfer reaction were extensively investigated (27)(28)(29). Furthermore, Aiuchi (30) and Anan'ev (31) reported that colloidal platinum nanoparticles as a catalyst could transfer electrons to hydrogen peroxide and hydrazine to cause them decompose in weakly alkaline solutions. As for the mechanism of hydrogen peroxide decomposition, many possible mechanisms for this catalysis have been proposed.…”
Section: Possible CL Enhancement Mechanism Discussionmentioning
confidence: 99%
“…However, the catalytic decomposition of hydrazine in the presence of platinum nanoparticles can take place on the surface of these nanoparticles by an electrophilic addition, that is, by forming electrophilic radicals which can then react with other hydrazine molecules from solution. [18] The presence of metallic platinum nanoparticles therefore implies the reduction of nickel complexes without the need for additional hydroxy groups present in solution. In fact, we observed that reduction of Ni 2+ did not occur in experiments using PAHfunctionalized CNTs in the absence of Pt nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the presence of Pt on the Au rods was essential to achieve the catalytic effect in nickel reduction and shell formation. The catalytic role of platinum seems to be related to the decomposition of hydrazine on the small nanoparticles, as discussed by Ershov et al, [37] who suggested the release of electrophilic radicals, which can react with other hydrazine molecules in solution. In the present case, in which hydrazine is partly complexed with Ni 2+ ions, [38] most of the non-complexed hydrazine can be catalytically decomposed on the platinum surface, leading to a charged metallic surface, where the Ni II complexes can be easily reduced to Ni 0 .…”
mentioning
confidence: 94%